Temperature-Dependent Friction-Induced Surface Amorphization Mechanism of Crystal Silicon - Qin, Jie (Langmuir : the ACS journal of surfaces and colloids, 2023)
Friction-induced surface amorphization of silicon is one of the most important surface wear and damage forms, changing the material properties and harming the reliability of silicon-based devices. However, knowledge regarding the amorphization mechanisms as well as the effects of temperature is still insufficient, because the experimental measurements of the crystal-amorphous interface structures and evolutions are extremely difficult. In this work, we aim to fully reveal the temperature dependence of silicon amorphization behaviors and relevant mechanisms by using reactive molecular dynamics simulations. We first show that the degree of amorphization is suppressed by the increasing temperature, contrary to our initial expectations. Then, we further revealed that the observed silicon amorphization behaviors are attributed to two independent processes: One is a thermoactivated and shear-driven amorphization process where the theoretical amorphization rate shows an interesting valley-like temperature dependence because of the competition between the increased thermal activation effect and the reduction of shear stress, and another one is a thermoactivated recrystallization process which shows a monotonically increasing trend with temperature. Thus, the observed reduction of amorphization with temperature is mainly due to the recrystallization effect. Additionally, analytical models are proposed in this work to describe both the amorphization and the recrystallization processes. Overall, the present findings provide deep insights into the temperature-dependent amorphization and recrystallization processes of silicon, benefiting the further development of silicon-based devices and technologies